Functional directions and strategic priorities of the structural policy of Ukraine. (Economics and region, 2016)
The system of key functional directions of the structural policy being responsible for transformation of the most significant components of the national economy structure was researched.
Keywords: Ukraine’s economy; structural policy; functional directions; strategic priorities; structural changes; economic development